At home in the world : a memoir - Maynard, Joyce, 1953- (New York : Picador USA, 1998)
"At Home in the World explores the story of Maynard's family, her relationship with [J.D.] Salinger, and the way the legendary writer's influence, along with that of her parents, reverberated through her life in the decades that followed. In these pages, she chronicles her painful reentry into the world, her development as a writer, her marriage, her struggle to become a healthy parent to her own children, the death of her parents, and the years, following the end of her marriage, when she set out to rebuild her life"
Keywords: Maynard, Joyce, -- 1953-; Salinger, J. D. -- 1919- -- Relations with women; Women authors, American -- 20th century -- Biography